Herbivore coprolites from the South-Central Andes: A multiproxy study at Los Viscos Archaeological Site, Catamarca, Argentina - Petrigh, Romina Sandra; Velázquez, Nadia Jimena; Fugassa, Martín Horacio; Burry, Lidia Susana; Mondini, Nora Mariana; Korstanje, María Alejandra (Elsevier, 2021)
Coprolites are among the faunal traces of the archaeological and paleontological fossil record. This is the first study of multiple proxies in herbivore coprolites from the South-Central Andes. The study includes Late Holocene samples from Los Viscos Archaeological Site in Catamarca, Argentina, of the last 2000 years. The aim of this study was to determine the zoological origin of the coprolites as an additional line of evidence to identify the fauna that entered the site. Pellet morphology, parasite contents, ancient DNA (aDNA) and pollen were analysed. Consistently with other reports of local faunal remains, most samples were determined as from Camelidae and Cetartiodactyla. Capra hircus was also identified close to a c. 400-year-old occupation, suggesting an early presence of this European herbivore in the region. Most of the identified parasite remains were taxon-specific. The identification of Fasciola hepatica eggs in goat coprolites provides early evidence of this parasite in domestic ruminants of the region, possibly from the early Hispanic-Indigenous contact. Regarding the diet items of these herbivores, the pollen spectra in the coprolites provide some clues to their management. These results have also allowed us to pose some palaeoecological hypotheses that will be tested in future research as well as to discuss some methodological implications of this multiproxy approach.